The Role of Employee Engagement in Mediating the Adoption of HR Technology on Employee Performance - Pohan, Amelia; Desy Surya, Elfitra; Farida Ferine, Kiki (International Conference Epicentrum of Economic Global Framework, 2026)
This study aims to analyze the role of employee engagement in mediating the effect of human resource technology adoption on employee performance at the Human Resources Bureau of the North Sumatra Regional Police. The development of digital technology in human resource management requires organizations not only to provide technological systems but also to ensure that employees can accept, use, and utilize these technologies optimally. In this study, employee engagement is positioned as an intervening variable that explains the mechanism of the relationship between HR technology adoption and improved employee performance. This study employs a quantitative approach with a population and sample of 115 employees from the Human Resources Bureau of the North Sumatra Regional Police, selected through saturation sampling. Data collection was conducted using a questionnaire with a Likert scale, while data analysis utilized the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the assistance of the SmartPLS software. Model testing was conducted through an outer model evaluation to assess the validity and reliability of the instruments, as well as an inner model evaluation to test the relationships among the research variables. The results indicate that HR technology adoption has a positive and significant effect on employee engagement, with a path coefficient of 0.419, a t-statistic of 7.239, and a p-value of 0.000. HR technology adoption also has a positive and significant effect on employee performance, with a path coefficient of 0.177, a t-statistic of 2.774, and a p-value of 0.006. Furthermore, employee engagement has a positive and significant effect on employee performance, with a path coefficient of 0.599, a t-statistic of 10.331, and a p-value of 0.000. The results of the indirect effect test indicate that HR technology adoption has a positive and significant effect on employee performance through employee engagement, with a coefficient of 0.251, a t-statistic of 5.617, and a p-value of 0.000.